Performance measure in a probabilistic re-entrant stress testing line using mean value analysis / Suresh Kumar and Mohamed Khaled Omar (Faculty of Mechanical Engineering and University Publication Centre (UPENA), 2006)
This paper presents a modified analytical model based on mean value analysis (MVA) technique and virtual lot clustering method for a probabilistic re-entrant stress testing line. The objective is to determine the total cycle time and the mean throughput rate of the Power Soak Testing (PST) process for a given number of lots. Using the analytical and simulation method, a five-stage queuing system with re-entrant lines into the second stage under various probabilistic routing conditions are analysed and comparison results are made. The results obtained can be used by operation managers for their decision-making.